The induced nontrivial Z2 topological phase in graphene sandwiched by pnictogen bilayers. (10th May 2016) - Shu, Cheng; Qu, Jinfeng; Peng, Xiangyang; Yang, Hong; Liu, Wenliang; Wei, Xiaolin; Zhang, Kaiwang; Zhong, Jianxin
Abstract: By performing first-principles calculations, we find that graphene with nearly zero spin orbit coupling can be turned into a topological insulator after being sandwiched between pnictogen bilayers. It is found that a dipole field is induced between graphene and pnictogen bilayers, which will significantly pull down the Dirac point of graphene. Depending on the initial position of the Dirac point of graphene with respect to the energy gap of the pnictogen bilayers, Bi/graphene/Bi is found to be a metallic system while Sb/graphene/Sb a topological insulator. In Sb/graphene/Sb, a sizable gap is opened at the Dirac point of graphene. The strong spin–orbit coupling in Sb bilayers leads to a band inversion in the gapped Dirac cones of graphene via the proximity effect and the calculated Z 2 topological index further confirms that a nontrivial topological phase is induced in graphene. By applying longitudinal or lateral strains to Sb/graphene/Sb, topological phase transition occurs based on the change of the thickness of the Sb bilayer instead of the change of the separation between graphene and Sb bilayers.